2022
DOI: 10.1136/bmjopen-2021-058793
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional association between gamma-glutamyl transferase and hyperuricaemia: the China Multi-Ethinic Cohort (CMEC) study

Abstract: ObjectivesSeveral studies have demonstrated the association between gamma-glutamyl transferase (GGT) and hyperuricaemia, but little is known about such relation in less-developed ethnic minority regions.DesignWe cross-sectionally analysed data from the China Multi-Ethnic Cohort (Yunnan region).SettingCross-sectional study.Participants22 020 participants aged 30–79 years from Han ethnicity, Yi ethnicity and Bai ethnicity.OutcomesThe serum level of uric acid, GGT and other metabolic parameters were tested. Weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Moreover, the high visceral fat content and strong stimulation of fatty acid synthesis is accompanied by hyper-metabolic conversion of ribose 5-phosphate in overweight /obese individuals, resulting in increased uric acid production 47 , as well as lower insulin sensitivity in overweight/obese individuals 48 , causing enhanced renal tubular re-absorption of uric acid and reduced uric acid excretion 49 . Epidemiological studies have also indicated that overweight and obesity are risk factors for elevated SUA 32 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the high visceral fat content and strong stimulation of fatty acid synthesis is accompanied by hyper-metabolic conversion of ribose 5-phosphate in overweight /obese individuals, resulting in increased uric acid production 47 , as well as lower insulin sensitivity in overweight/obese individuals 48 , causing enhanced renal tubular re-absorption of uric acid and reduced uric acid excretion 49 . Epidemiological studies have also indicated that overweight and obesity are risk factors for elevated SUA 32 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HUA in China ranges from 13.7 to 18.8% in different regions [ 5 ]. Of note, the prevalence of HUA is mostly driven by lifestyle, such as an unhealthy diet [ 6 ], sleep deprivation [ 7 ] or unfavourable lipid profiles [ 8 ].…”
Section: Introductionmentioning
confidence: 99%